2014
DOI: 10.5120/16183-5415
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Various Feature Detector and Descriptor for Real-Time Video based Face Tracking

Abstract: This paper presents the performance analysis of various contemporary feature detector and descriptor pair for real time face tracking. These feature detectors/descriptors are mostly used in image matching applications. Some feature detectors/descriptors like STAR, FAST, BRIEF, FREAK, and ORB can also be used for SLAM applications due to their high performance. However using only one of these feature detectors for object tracking may not provide good accuracy due to various challenges in tracking like abrupt ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Feature extraction algorithms can be designed for the purpose of feature detection only (like AGAST [17], FAST [18], and STAR [19]), feature description only (like BEBLID [20], BRIEF [21], DAISY [22], FREAK [23], LATCH [24], LUCID [25], TEBLID [26], and VGG [27]), or both feature detection and description (like AKAZE [28], BRISK [29], KAZE [30], ORB [31], SIFT [32], and SURF [33]). In this paper, algorithms that were designed for feature detection are combined with algorithms that were designed for feature description.…”
Section: Feature Detectors and Descriptorsmentioning
confidence: 99%
“…Feature extraction algorithms can be designed for the purpose of feature detection only (like AGAST [17], FAST [18], and STAR [19]), feature description only (like BEBLID [20], BRIEF [21], DAISY [22], FREAK [23], LATCH [24], LUCID [25], TEBLID [26], and VGG [27]), or both feature detection and description (like AKAZE [28], BRISK [29], KAZE [30], ORB [31], SIFT [32], and SURF [33]). In this paper, algorithms that were designed for feature detection are combined with algorithms that were designed for feature description.…”
Section: Feature Detectors and Descriptorsmentioning
confidence: 99%
“…An algorithm called enhanced affline transformation (EAT) is presented for "non-rigid infrared (IR) and visible (VIS)" image registration [18]. In order to carry out research in real time visual face tracking applications, a number of feature detector and descriptor pairs can be utilized [19]. A novel feature matching scheme is proposed in [20] which is spatially invariant.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, we have compiled our conclusion and future work in this area in Section 5. Kulkarni et al (2013), Patel et al (2014) and Yu et al (2015) suggested contrast-based picture coordinating, which is a vital part of numerous PC-based applications. Distinctive calculations are utilised for picture handling like SIFT, speeded up robust features (SURF), oriented features from accelerated segment test (FAST) and rotated binary robust independent elementary feature (BRIEF) (ORB), ORB calculation utilises the oFAST calculation to distinguish the component focuses, which is the FAST administrator that has bearing.…”
Section: Introductionmentioning
confidence: 99%